INTERPRETATIVE PHENOMENOLOGICAL ANALYSIS TO EXPLORE FATHERS’ EXPERIENCE WITH A CHILD IN PALLIATIVE CARE - Zuitiņš, Juris; Pipere, Anita; Sudraba, Velga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Phenomenological research is commonly used worldwide in the field of health psychology to describe and explain the unique life experiences of health and disease. In Latvia, the phenomenological research in health psychology has not been performed yet. In this study, the methodological aspects of interpretative phenomenological analysis applied to explore the experience of fathers with a child in palliative care will be exemplified. The paper particularly aims to analyze the steps of interpretative phenomenological analysis applied during the study of one father’s experience. A single case will be presented detailing the disclosure of father’s experience and reflection on the process of interpretive phenomenological analysis on interview data. Conclusions in terms of the methodological aspects of interpretative phenomenological analysis will be provided.